"They have to toe the line": a Foucauldian analysis of the socialisation of former elite athletes into academy coaching roles. Issue 1 (2nd January 2019) - Blackett, A. D.; Evans, A. B.; Piggott, D.
Abstract: The pathway between elite athlete and high-performance coach is common within English men's rugby union and association football. To help develop as coaches, many elite athletes gain coaching experiences within male high-performance youth academies. The purpose of this article sought to gain an insight into the socialisation processes of current and former elite athletes within association football and rugby union amongst the socio-cultural context of England, and to identify why Academy Directors seemingly preferred to recruit current and former elite athletes as academy coaches. Semi-structured interviews with 11 Academy Directors were conducted. Results showed that the Academy Directors preferred to recruit their respective club's current and former athletes as a means to govern their academy's "club culture". Foucault's concepts of docility and discipline conceptualise how current and former elite athletes were judged to be more trustworthy to reproduce the academy culture in their coaching practices compared to external candidates.